Enhanced hetero‐elements doping content in biomass waste‐derived carbon for high performance supercapacitor. (22nd August 2019) - Fang, Ju; Guo, Di; Kang, Chenxia; Wan, Shuyun; Li, Shuxian; Fu, Likang; Liu, Gang; Liu, Qiming
Summary: Betel nut wastes are firstly modified with nitric acid/thiourea to fabricate hetero‐element doping carbon (C‐H‐T) for energy storage. C‐H‐T exhibits improved content of O (12.27%), N (2.52%), and S (2.88%) compared with that of purely carbonized carbon with O (9.2%) and N (1.76%). Without nitric acid heat treatment, the carbon materials prepared by hydrothermal treatment with thiourea only get increasing hetero‐elements content of O (10.46%), N (2.9%), and S (0.53%). The similar results have been obtained using urea and melamine as dopants. Due to the synergistic effects of the hetero‐elements containing functional groups, C‐H‐T get a significant enhancement in its electrochemical properties with a high capacitance (423 F g −1 at 0.5 A g −1 ) in KOH electrolyte. C‐H‐T based coin‐type symmetric supercapacitors display maximum energy density of 61.7 Wh kg −1 and considerate cycling ability with 94% capacitance retention after 10 000 cycles. The fabricated two‐step method can inspire the increase of hetero‐elements content in carbon materials to develop its application in energy storage. Abstract : Betel nut wastes are firstly modified by nitric acid treatment and hydrothermal doping. Triple doping of oxygen, nitrogen, and sulfur. Enhanced hetero‐elements doping content and high specific capacitance.